THE INFLUENCE OF PRODUCT PRICE AND QUALITY ON CONSUMER PURCHASING DECISIONS ON ABC (CRAFT HEINZ) PRODUCTS IN PADANG CITY - Rahmadani Rahmadani; Jumriah Basri (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to find out about the influence of product quality and price on consumer purchase decisions on ABC (Craft Heinz) products in Padang City. The type of research used in this study is quantitative descriptive. The population used in this study was 50 respondents. The sample in this study is customers who have used ABC (Craft Heinz) products 1 time in the city of Padang. The sampling technique used is nonprobability sampling with a data collection method using a questionnaire. The data analysis technique in this study uses multiple linear regression. Based on the results of this study, product quality and price have a positive and significant effect on consumer purchase decisions on ABC (Craft Heinz) products in Padang City.